The command [videorecording (DVD)] - Rodat, Robert; Moore, Robert; Schoenaerts, Matthias, 1977-; Seydoux, Léa, 1985-; Firth, Colin, 1960-; Simonischek, Peter; Diehl, August, 1976-; Moore, Robert (Saban Brands : Lionsgate, 2019)
Follow the final hours of an 'unsinkable' Russian nuclear submarine as it sinks to the bottom of the Barents Sea. Some of the crew survives the initial explosion, including officer Mikhail Kalekov, whose pregnant wife and child are waiting back home. Unfortunately, their rescue is complicated by bureaucracy between Russia, France, Norway, and Britain, with British navy chief David Russell attempting to convince Russian officials to accept foreign aid.